Makna Komitmen dalam Lirik Lagu “Promise” Karya EXO: (Analisis Semiotika Charles Sanders Peirce) - I Wayan Suartawan; Melina Sefani; Astuti Wijayanti (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
Songs as a form of artistic expression have the power to convey deep emotional messages. One of the works that is full of meaning is "Promise" by EXO, which not only serves as entertainment but also as a medium of communication between artists and fans. This study aims to analyze the meaning of commitment in the lyrics of the song "Promise" using Charles Sanders Peirce's semiotic approach. The method used is qualitative descriptive, by interpreting the signs in the lyrics as representations, objects, and interpretants. The results of the analysis show that the lyrics of this song contain messages about loyalty, regret, and determination to stay together in any condition. Commitment is represented as a form of emotional responsibility and a strong desire to improve oneself and maintain relationships. In addition, this study relates the meaning of commitment in songs to interpersonal communication, emphasizing that music can be an effective and profound means of communication in conveying personal and collective messages. These findings show that popular music can serve as a medium for emotional reflection while strengthening the social bond between artists and listeners.